Քրդական հարցի ներկա վիճակը եվ զարգացման միտումները - Բայբուրդյան Վահան (YSU Journal of International Affairs, 2017)
The article deliberates on the Kurdish issue within so-called ethnic Kurdistan including relevant territories in Turkey, Iran, Iraq and Syria. It is emphasized that Kurds are currently the biggest ethnic group in the Middle and Central East lacking statehood. The idea is highlighted that the war now in progress in Syria has brought fresh blood into the national Kurdish movement. The article analyzes the activities of Kurdish political parties and organizations; the perspectives of the Kurdish issue; as well as the policy of the USA and the European Union towards this complex and intricate question. It is noteworthy that Kurds are currently one of the key factors in the politics of the Middle and Central East.